ANALISIS RISIKO PADA PELAKSANAAN PROYEK PEMBANGUNAN PUSAT KULINER STASIUN STREET FOOD BUKITTINGGI - Koes Mutiara, Nafa; Kurniawan, Deddy; Zulhedi, Zulhedi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
There are various kinds of development projects in construction projects in Bukittinggi, one of which is the construction of a culinary center, The project location is in the city center area, and around the project there are many people selling it is important to identify undesirable risks so that they do not hinder or cause failure in the implementation of the project. Data analysis using the Severity Index method has the aim of determining the probability (P) and impact (I) categories. SI calculated based on the answers of all respondents. Next, they are categorized based on the magnitude of the probability and impact calculation results into the Probability Impact Matrix, which describes the level of risk that has been identified. Evaluation of the probability and impact of each risk is carried out using a probability and impact matrix which determines the combination of probability and impact that leads to the lowest, medium risk level. , or high. The results of the analysis showed that 1 risk was in the low category, 2 risks were in the high category, namely errors in the initial survey and errors in cost estimates. 15 risks are in the medium category, which is the dominant risk level. For risk response to high risk levels, it is necessary to consider minimizing errors by transferring them because if an error occurs it will have a huge impact on project .Keywords: risk;severity index; probability.